Prognostic significance of prognostic nutritional index in patients with head and neck squamous cell carcinoma - Wang, Yongping; Wang, Jie; Xiao, Binbin; Wang, Yuqing; Huang, Fu; Jiang, Yang; Liu, Tianyi (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the relationship between prognostic nutritional index (PNI) and prognosis in patients with head and neck squamous cell carcinoma (HNSCC).MethodsA systematic review was conducted across three major databases—Embase, PubMed, and the Cochrane Library—to identify studies examining the association between PNI and outcomes in HNSCC patients. The search included all records from database inception through January 20, 2025. Outcomes assessed included hazard ratios (HRs) for overall survival (OS), cancer-specific survival (CSS), disease-free survival (DFS), and progression-free survival (PFS), as well as odds ratios (ORs) for objective response rate (ORR) and disease control rate (DCR).ResultsA total of 27 articles involving 4,400 patients were included. Patients with low PNI had significantly shorter OS (HR: 2.42, 95% CI: 2.15–2.73, p < 0.001), CSS (HR: 2.05, 95% CI: 1.09–3.84, p = 0.026), DFS (HR: 1.89, 95% CI: 1.58–2.27, p < 0.001), and PFS (HR: 2.23, 95% CI: 1.90–2.62, p < 0.001) compared to those with high PNI. Additionally, low PNI was associated with lower ORR (OR: 0.40, 95% CI: 0.22–0.73, p = 0.002) and DCR (OR: 0.30, 95% CI: 0.17–0.53, p < 0.001). Subgroup analyses confirmed consistent associations between PNI and OS, DFS, and PFS across different Cox models, cancer types, treatment modalities (immune checkpoint inhibitors and surgery), countries, and PNI cut-off values.Clinical trial registrationThis study underscores the prognostic significance of PNI in predicting survival outcomes and treatment responses in HNSCC patients. The findings highlight the importance of incorporating PNI into routine prognostic assessments to improve clinical decision-making and patient management in HNSCC.